Conscious communication and mental health: dual technique: suffering vs pain, for the improvement of stress - Vargas Delgado, José Jesús; Sacaluga Rodríguez, Ignacio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The objectives of study will be based on deepening the limiting concept that stress is a consequence of circumstances external to us such as those generated by the Covid-19 pandemic, but it is born depending on the communicative way in which we evaluate the events, or our capacities to face and discern the duality of pain (primary suffering) and suffering (secondary suffering). The proposal of the dualistic technique of pain vs. Suffering is a research continuity of the Stress 0.0 program. a practical methodology to reduce stress to its minimum expression.